Challenging the Misnomer of Irreversible Pulpitis and Deliberating the Urgent Need for Reclassification of Pulpal Diseases Based on the Efficacy of Vital Pulp Therapies: An Overview of Systematic Reviews - Asgary, Saeed; Eghbal, Mohammad Jafar (Iranian Endodontic Journal, 2023)
Over recent decades, the definition of irreversible pulpitis (IP), as an irrevocable condition of a compromised dental pulp tissue, has forced clinicians towards invasive root canal treatments. However, the current best evidence challenges the alignment between clinical symptoms and the perceived irreversibility of a negotiated dental pulp tissue. In the above-mentioned context, vital pulp therapy (VPT) has emerged as a revolutionary and transformative approach; introducing minimally invasive techniques to sustain pulp vitality in cases of IP. The present paper aimed to rigorously examine the corresponding published systematic reviews to explore the diverse spectrum of VPT modalities and their outcomes in managing IP cases. Besides, the current review seems to have asserted the need to discard the conventional terminology of irreversible pulpitis, based on the effectiveness of VPTs in the achievement of pulp tissue healing within cases clinically diagnosed as IP.